Philosophy of Praxis and Education in Gramsci - Baldacci, Massimo (International Gramsci Journal, 2025)
The paper examines Gramsci's pedagogy in the Prison Notebooks, arguing that it cannot be isolated but must be understood within the context of his overall thought. The author identifies the philosophy of praxis as a central source, emphasizing its active role in transforming reality. This philosophy, inherently critical, assumes a formative perspective in Gramscian thought. Specifically, it highlights the educational struggle against folklore for an advanced conception of the world. The paper also explores the pedagogical prerequisites for transforming common sense into higher culture, linking the active pedagogical relationship to Gramsci's concept of hegemony. Mutual understanding between intellectuals and the populace is essential for guiding the popular element from passion to knowledge. Finally, the paper analyzes the dialectical nature of education in Gramsci. In particular, he highlights the role of culture as an object in transforming the subject, promoting genuine intellectual reform. This approach is tied to the emancipation of the subalterns, achieved through an educational dialectic that surpasses puerocentric and epistemocentric unilateralities.